Fatty acid 16:4(n‐3) stimulates a GPR120‐induced signaling cascade in splenic macrophages to promote chemotherapy resistance. Issue 5 (9th February 2017) - Houthuijzen, Julia M.; Oosterom, Ilse; Hudson, Brian D.; Hirasawa, Akira; Daenen, Laura G. M.; McLean, Chelsea M.; Hansen, Steffen V. F.; van Jaarsveld, Marijn T. M.; Peeper, Daniel S.; Sadatmand, Sahar Jafari; Roodhart, Jeanine M. L.; van de Lest, Chris H. A.; et al.
ABSTRACT: Although chemotherapy is designed to eradicate tumor cells, it also has significant effects on normal tissues. The platinum‐induced fatty acid 16: 4(n‐3) (hexadeca‐4, 7, 10, 13‐tetraenoic acid) induces systemic resistance to a broad range of DNA‐damaging chemotherapeutics. We show that 16: 4(n‐3) exerts its effect by activating splenic F4/80 + /CD11b low macrophages, which results in production of chemoprotective lysophosphatidylcholines (LPCs). Pharmacologic studies, together with analysis of expression patterns, identified GPR120 on F4/80 + /CD11b low macrophages as the relevant receptor for 16: 4(n‐3). Studies that used splenocytes from GPR120‐deficient mice have confirmed this conclusion. Activation of the 16: 4(n‐3)‐GPR120 axis led to enhanced cPLA2 activity in these splenic macrophages and secretion of the resistance‐inducing lipid mediator, lysophosphatidylcholine(24: 1). These studies identify a novel and unexpected function for GPR120 and suggest that antagonists of this receptor might be effective agents to limit development of chemotherapy resistance.—Houthuijzen, J. M., Oosterom, I., Hudson, B. D., Hirasawa, A., Daenen, L. G. M., McLean, C. M., Hansen, S. V. F., van Jaarsveld, M. T. M., Peeper, D. S., Jafari Sadatmand, S., Roodhart, J. M. L., van de Lest, C. H. A., Ulven, T., Ishihara, K., Milligan, G., Voest, E. E. Fatty acid 16: 4(n‐3) stimulates a GPR120‐induced signaling cascade in splenic macrophages to promote chemotherapy resistance. FASEB J. 31, 2195–2209 (2017). www.fasebj.org